Hypertonic saline resuscitation after emergent laparotomy and temporary abdominal closure. Issue 2 (February 2018) - Loftus, Tyler J.; Efron, Philip A.; Bala, Trina M.; Rosenthal, Martin D.; Croft, Chasen A.; Smith, R. Stephen; Moore, Frederick A.; Mohr, Alicia M.; Brakenridge, Scott C.
Abstract : BACKGROUND: Our objective was to establish the safety of 3% hypertonic saline (HTS) resuscitation for trauma and acute care surgery patients undergoing emergent laparotomy and temporary abdominal closure (TAC) with the hypothesis that HTS administration would be associated with hyperosmolar hypercholoremic acidosis, lower resuscitation volumes, and higher fascial closure rates, without adversely affecting renal function. METHODS: We performed a retrospective cohort analysis of 189 trauma and acute care surgery patients who underwent emergent laparotomy and TAC, comparing patients with normal baseline renal function who received 3% HTS at 30 mL/h (n = 36) to patients with standard resuscitation (n = 153) by baseline characteristics, resuscitation parameters, and outcomes including primary fascial closure and Kidney Disease: Improving Global Outcomes stages of acute kidney injury. RESULTS: The HTS and standard resuscitation groups had similar baseline illness severity and organ dysfunction, though HTS patients had lower serum creatinine at initial laparotomy (1.2 mg/dL vs. 1.4 mg/dL; p = 0.078). Forty-eight hours after TAC, HTS patients had significantly higher serum sodium (145.8 mEq/L vs. 142.2 mEq/L, p < 0.001), chloride (111.8 mEq/L vs. 106.6 mEq/L, p < 0.001), and osmolarity (305.8 mOsm/kg vs. 299.4 mOsm/kg; p = 0.006), and significantly lower arterial pH (7.34 vs. 7.38; p = 0.011). The HTS patients had lower intravenous fluid (IVF) volumes within 48 hours of TAC (8.5 L vs. 11.8 L; p = 0.004). Serum creatinine, urine output, and kidney injury were similar between groups. Fascial closure was achieved for 92% of all HTS patients and 77% of all standard resuscitation patients ( p = 0.063). Considering all 189 patients, higher IVF resuscitation volumes within 48 hours of TAC were associated with decreased odds of fascial closure (odds ratio, 0.90; 95% confidence interval, 0.83–0.97; p = 0.003). CONCLUSION: Hypertonic saline resuscitation was associated with the development of a hypernatremic, hyperchloremic, hyperosmolar acidosis, and lower total IVF resuscitation volumes, without adversely affecting renal function. These findings may not be generalizable to patients with baseline renal dysfunction and susceptibility to hyperchloremic acidosis-induced kidney injury. Level of Evidence: Prognostic study, level II. Abstract : Supplemental digital content is available in the text.